Multiplex PCR provides a low-cost alternative to DNA probe methods for rapid identification of Mycobacterium avium and Mycobacterium intracellulare. - Cousins, D (1996)
A multiplex PCR designed to differentiate Mycobacterium tuberculosis complex organisms from M. avium and M. intracellulare was used to test 105 isolates identified by DNA probe methods as M. avium, M. intracellulare, or M. avium complex type X. The multiple PCR correctly identified 33 of 34 isolates identified by commercial probe methods as M. avium and all 51 isolates identified as M. intracellulare. The 20 isolates identified as M. avium complex type X by probe were identified as Mycobacterium spp. by the multiplex method. These results confirm that the multiplex PCR, which is simple to perform and cheaper than commercial probe methods, is suitable for routine identification of M. avium and M. intracellulare.